A Hybrid MAGDM Approach of Neutrosophic TOPSIS - LINMAP method for developing Enterprise Selection Criteria - Tamilarasi, G; Paulraj, S; Sivanandha Saraswathy, M; Thanuja, T.S (Neutrosophic sets and systems, 2025)
Multi-attribute group decision-making (MAGDM) problems have traditionally been addressed using approaches like the standard LINMAP and TOPSIS. However, existing studies utilizing these methods often face challenges in handling uncertain, vague, and incomplete data, especially when working with fuzzy or intuitionistic environments. Additionally, traditional methods have limitations in modeling and computing with more complex, nuanced information such as neutrosophic numbers, which are better suited for capturing the indeterminacy inherent in real-world decision-making problems. In this research, we provide a novel approach to handle MAGDM problems under a SVTN number framework, extending the classic LINMAP approach to the neutrosophic context. The new method overcomes the shortcomings of existing techniques by providing a more robust decision-making model that incorporates neutrosophic uncertainty. Furthermore, we propose an integrated approach combining neutrosophic LINMAP with TOPSIS, offering a comprehensive solution to MAGDM problems that is more adaptable to practical enterprise selection scenarios. This method is intended to increase decision-making accuracy and dependability when faced with ambiguous and insufficient information. The usefulness of the suggested technique is illustrated by a real-world example that shows how the integrated neutrosophic LINMAP-TOPSIS strategy may be used for enterprise selection and produces better outcomes than standard techniques. Keywords: Single valued trapezoidal neutrosophic number; decision making; Neutrosophic Linear programming technique for multidimensional analysis of preference; Hamming distance;Relative closeness coefficient; Consistency and inconsistency measurements; Borda's scores